2022
DOI: 10.1021/acsomega.2c07157
|View full text |Cite
|
Sign up to set email alerts
|

Combined Neutrase–Alcalase Protein Hydrolysates from Hazelnut Meal, a Potential Functional Food Ingredient

Abstract: Consumers' interest in functional foods has significantly increased in the past few years. Hazelnut meal, the main valuable byproduct of the hazelnut oil industry, is a rich source of proteins and bioactive peptides and thus has great potential to become a valuable functional ingredient. In this study, hazelnut protein hydrolysates obtained by a single or combined hydrolysis by Alcalase and Neutrase were mainly characterized for their physicochemical properties (SDS-PAGE, particle size distribution, Fourier-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The conformational structures of ISMP and alcalase-hydrolyzed ISMPH were characterized by spectroscopy techniques in Figure . FTIR spectroscopy is one of the widely applied and well-established methods for the structural characterization of proteins and peptides. , As shown in Figure A, ISMP and ISMPH had similar functional groups with absorption peaks of O–H and N–H (3409.01 and 3392.2 cm –1 ), −CH 2 – (2927.23 and 2927.12 cm –1 ), amide I band/CO (1655.22 and 1659.11 cm –1 ), −COOH (1402.86 and 1403.27 cm –1 ), amide III/C–O (1241.95 and 1244.25 cm –1 ), and C–O/C–C–C/C–N (1033.99 and 1034.95 cm –1 ), respectively . And it was observed that ISMP had an absorption peak of the amide II band at 1546.14 cm –1 , which was higher than that of ISMPH ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The conformational structures of ISMP and alcalase-hydrolyzed ISMPH were characterized by spectroscopy techniques in Figure . FTIR spectroscopy is one of the widely applied and well-established methods for the structural characterization of proteins and peptides. , As shown in Figure A, ISMP and ISMPH had similar functional groups with absorption peaks of O–H and N–H (3409.01 and 3392.2 cm –1 ), −CH 2 – (2927.23 and 2927.12 cm –1 ), amide I band/CO (1655.22 and 1659.11 cm –1 ), −COOH (1402.86 and 1403.27 cm –1 ), amide III/C–O (1241.95 and 1244.25 cm –1 ), and C–O/C–C–C/C–N (1033.99 and 1034.95 cm –1 ), respectively . And it was observed that ISMP had an absorption peak of the amide II band at 1546.14 cm –1 , which was higher than that of ISMPH ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the study conducted by Fathi et al ( 2021 ) indicates that prolonging the incubation time allows for a more extensive action of alcalase on the protein, resulting in heightened extraction efficiency and increased cleavage of peptide bonds (Gong et al 2021 ). Consequently, these factors significantly enhance extraction efficiency (Ceylan et al 2023 ). Furthermore, the relationship between the degree of hydrolysate and protein extraction efficiency is evident.…”
Section: Resultsmentioning
confidence: 99%
“…As proteolytic enzymes can differ in cleavage sites, the combination of proteolytic enzymes can sometimes be applied to generate protein hydrolysates with more diverse peptides and ultimately more attractive properties than individual enzymes. For instance, hazelnut protein isolate treated with both Alcalase and Neutrase displayed a higher antioxidant capacity than that treated with individual Alcalase and Neutrase [ 16 ]. The utility of two enzymes (pepsin-papain, papain-trypsin and papain-pancreatin) has been reported for EBN hydrolysis.…”
Section: Introductionmentioning
confidence: 99%